Can increased tax transparency curb corporate tax avoidance? - Michael Razen; Alexander Kupfer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Tax avoidance among large multinational corporations has considerably increased in recent years, triggering an intense discussion about how to ensure tax justice. We propose a novel experimental design to incentive-compatibly model the firm-consumer relationship in a consumer goods market. This new paradigm allows us to analyze the effect of increased tax transparency on consumer and firm behavior in a dynamic framework. We find that absent the threat of being exposed as a tax avoiding firm, only 26% of the firms decide to pay taxes. Once tax avoiding firms are identifiable in the market, this rate rises to 58%. Providing market participants additionally with information about the social costs of tax avoidance increases the fraction of tax paying firms further to 74%. We show that these improvements are the consequence of firms proactively adopting tax responsible behavior and, at the highest level of transparency, consumers showing a stronger proclivity to boycott tax avoiding firms, even if these firms offer cheaper prices. Our results confirm the effectiveness of increased transparency to curb corporate tax avoidance.
Keywords: C9; C92; H26; 330; economic experiment; tax avoidance; public good dilemma; consumer behavior; firm behavior